Conductive Fiber‐Based Ultrasensitive Textile Pressure Sensor for Wearable Electronics. (18th February 2015) - Lee, Jaehong; Kwon, Hyukho; Seo, Jungmok; Shin, Sera; Koo, Ja Hoon; Pang, Changhyun; Son, Seungbae; Kim, Jae Hyung; Jang, Yong Hoon; Kim, Dae Eun; Lee, Taeyoon
<x xml:space="preserve">Abstract</x> A flexible and sensitive textile‐based pressure sensor is developed using highly conductive fibers coated with dielectric rubber materials. The pressure sensor exhibits superior sensitivity, very fast response time, and high stability, compared with previous textile‐based pressure sensors. By using a weaving method, the pressure sensor can be applied to make smart gloves and clothes that can control machines wirelessly as human–machine interfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>